KS-cSCC-1 and KS-cSCC-2: two novel cutaneous squamous cell carcinoma cell lines established from Japanese patients - Ito, Takamichi; Tanaka, Yuka; Kaku-Ito, Yumiko; Tanegashima, Keiko; Imajima, Mao; Ichiki, Toshio; Nakahara, Takeshi (Frontiers in Medicine, 2024)
Introduction Cutaneous squamous cell carcinoma (cSCC) is a common form of skin cancer. Less accessibility to the cSCC cell lines has limited analyses of this disease. Thus, we here aimed to establish novel cSCC cell lines from patient's cSCC lesions. Methods Two novel cSCC cell lines (named KS-cSCC-1 and KS-cSCC-2) were established from an axillary lymph node metastasis of a Japanese female and an inguinal lymph node metastasis of a Japanese male. The characteristics of the established cell lines were assessed by in vitro analyses. Results The cells were successfully maintained for more than 9 months, with a doubling time of 47.5 ± 1.11 h (KS-cSCC-1) and 39.2 ± 5.78 h (KS-cSCC-2). The cell lines exhibited constant growth, spheroid formation, and invasiveness. Short tandem repeat analyses and immunohistochemistry confirmed that both cell lines are identical to their original tumor. The KS-cSCC-1 cells were weakly positive for CK14 and strongly positive for CK10, while the KS-cSCC-2 showed opposite expression patterns. Chemosensitivity of the cell lines was further tested and the cells were sensitive to anticancer drugs which are used to treat cSCC. Conclusion The KS-cSCC-1 and KS-cSCC-2 cell lines were promising resources for basic and preclinical research on cSCC to better define the tumor characteristics and treatment strategy of this cancer.